2021
DOI: 10.1007/s00420-021-01728-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequent short sickness absence, occupational health service utilisation and long-term sickness absence due to mental disorders among young employees

Abstract: Objectives We examined whether frequent short-term sickness absence (FSTSA) and primary care use in occupational health service (OHS) were associated with medically-certified long-term sickness absence (LTSA) due to mental disorders among young employees. Methods We used record-linkage data covering the young employees (< 35 years) of the City of Helsinki, Finland (n = 8,282) from 2010 to 2014. The outcome was LTSA due to mental disorders. Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Different rates of sickness absence (SA) among those employed in private and public sectors have been previously reported in several countries 1 3 . However, knowledge is still scarce on rates of SA among young employees in private and public sectors, a group of individuals where SA due to mental disorders is most common both in Sweden and other Nordic countries 4 – 9 . Understanding factors contributing to SA differences between young adults employed in private and public sectors may help to identify factors affecting future SA as well as promoting working force participation.…”
Section: Introductionmentioning
confidence: 99%
“…Different rates of sickness absence (SA) among those employed in private and public sectors have been previously reported in several countries 1 3 . However, knowledge is still scarce on rates of SA among young employees in private and public sectors, a group of individuals where SA due to mental disorders is most common both in Sweden and other Nordic countries 4 – 9 . Understanding factors contributing to SA differences between young adults employed in private and public sectors may help to identify factors affecting future SA as well as promoting working force participation.…”
Section: Introductionmentioning
confidence: 99%
“…Separating long-term SA from total SA enables distinguishing work absenteeism due to medically verified illness which is strongly linked to future disability retirement [ 20 ]. As part of the total SA data, we considered short-term SA spells, which are common, have financial implications, and confer a higher risk of long-term SA [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis-specific Finnish national register data exists for long-term SA, which is strongly linked to later disability retirement [ 20 ]. Moreover, frequent shorter SA spells are associated with long-term SA due to mental disorders among younger employees [ 21 ]. Thus, the total SA burden is also relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term SA (1–14 days) is mainly considered to be absence caused by minor infectious diseases and indolent conditions. 9 Contrary to this, studies on municipal employees have identified that earlier short-term SA precedes long-term SA 10 , 11 and permanent work disability. 12 It has also been proposed as a coping behaviour to deal with work-related strain.…”
Section: Introductionmentioning
confidence: 88%
“…We modelled short-term SA using spells instead of cumulative short-term SA days, since previous research suggests that work disability is initially marked by recurring short-term SA spells. 10 , 11 , 24 Long-term SA days per year were transformed to account for months due to analytical purposes as follows: 0–13 days = 0 months, 14–29 days = 1 month, 30–59 days = 2 months, etc., and 12 months = 330 or more SA days.…”
Section: Methodsmentioning
confidence: 99%